"Aerogels of enzymatically oxidized galactomannans from leguminous plants: Versatile delivery systems of antimicrobial peptides and enzymes". (20th February 2017) - Campia, Paola; Ponzini, Erika; Rossi, Bianca; Farris, Stefano; Silvetti, Tiziana; Merlini, Luca; Brasca, Milena; Grandori, Rita; Galante, Yves M.
Highlights: Aerogels were obtained by lyophilization of laccase-oxidized galactomannans (GM). GM's were from: fenugreek, sesbania and guar, with decreasing galactose content. The mechanical properties and porosity of these aerogels were studied. Sesbania and guar yielded similar aerogels, while fenugreek a more stable one. They were all evaluated as delivery systems (DS) of absorbed and released actives. The actives tested were: polymyxin B, nisin, lysozyme, a protease and a lipase. These biomaterials could be developed as biocompatible DS of active principles. Abstract: We describe aerogels obtained by laccase/TEMPO-oxidation and lyophilization of galactomannans (GM) from fenugreek, sesbania and guar. Enzymatic oxidation of GM in aqueous solution caused viscosity increase up to fifteen-fold, generating structured, elastic, stable hydrogels, presumably due to establishment of hemiacetalic bonds between newly formed carbonyl groups and free hydroxyl groups. Upon lyophilization, water-insoluble aerogels were obtained, whose mechanical properties and porosity were investigated. Active principles were absorbed into the aerogels from aqueous solutions and, following rinsing, blotting, re-lyophilization, were released in an appropriate medium. The release of the antibiotic polymyxin B was tested against six different Gram-negative bacterial strains, of the antimicrobial peptide nisin against two Gram-positive and of the muraminidase lysozyme against one anaerobic strain. Protease and lipase release in solution from "enzyme loaded" aerogels was monitored by the increase in enzymatic activity. These biomaterials could represent new versatile, biocompatible "delivery systems" of actives for biomedical and industrial applications.